Manfaat Media Komunikasi Dalam Pembelajaran Pada Kelas IV B SD IT Ar-Ridha Pantai Cermin, Tanjung Pura - Dila Aulia; Muhammad Sulaiman; Syahera; Tuti Rezeki Awaliyah Siregar (STIT Fatahillah, 2024)
This research aims to evaluate the benefits of using communication media in learning in class IV B SD IT Arridha Pantai Cermin. The research method used is a descriptive method with a qualitative approach by collecting data through indepth interviews and observations of the implementation of communication media in the learning process. The results of the research show that the use of audiovisual and audio communication media in learning in class IV B SD IT Arridha Pantai Cermin has proven effective in accommodating various student learning styles, increasing involvement and collaboration between students and teachers, therefore the focus of this research is to explore how teachers, especially Mrs. Khadijah, S.Pd, utilize this technology to increase the interactivity and effectiveness of learning in the classroom.